The components of passive knee movement are coupled to flexion angle. - Wilson, DR; Feikes, J; Zavatsky, A; O'Connor, J (2000)
Movement of the unloaded knee has been described in several studies by an "envelope of passive flexion", a description that does not describe or explain the widely reported coupling of internal tibial rotation to flexion. The objective of the current study was to show that the envelope of passive knee flexion can be reduced to a coupled path. Two hypotheses were tested: (1) in normal knees flexed passively, internal/external rotation, abduction/adduction and all three components of translation are coupled to flexion angle, and (2) the tibia rotates internally as the knee is flexed passively. Fifteen cadaver knees were flexed in a rig designed to apply minimal resistance to knee movement while three-dimensional kinematics of the femur relative to the tibia were measured with an electromagnetic tracking system. Each specimen displayed internal tibial rotation and posterior, proximal and medial displacement of a reference point with flexion, while a range of ab/adduction behaviour was observed. Mean absolute differences between the flexing and extending paths in normal specimens were under 2 and 0.2 degrees for internal/external tibial rotation and ab/adduction, respectively. Deviation from the movement path was resisted: when released after being displaced, the femur of each normal joint sprang back to its original position on the motion path. It was concluded that passive knee flexion can be described by a coupled path. Although the exact shape of the path is very sensitive to load and varies between knees, knee rotations and translations were always coupled to flexion, and internal tibial rotation with flexion was always observed.